Studies of beauty suppression via nonprompt D-0 mesons in Pb-Pb collisions at root s(NN)=5.02 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (American Physical Society, 2019)
The transverse momentum spectra of D0 mesons from b hadron decays are measured at midrapidity (jyj < 1) in pp and Pb-Pb collisions at a nucleon-nucleon center of mass energy of 5.02 TeV with the CMS detector at the LHC. The D0 mesons from b hadron decays are distinguished from prompt D0 mesons by their decay topologies. In Pb-Pb collisions, the B → D0 yield is found to be suppressed in the measured pT range from 2 to 100 GeV=c as compared to pp collisions. The suppression is weaker than that of prompt D0 mesons and charged hadrons for pT around 10 GeV=c. While theoretical calculations incorporating partonic energy loss in the quark-gluon plasma can successfully describe the measured B → D0 suppression at higher pT, the data show an indication of larger suppression than the model predictions in the range of 2 < pT < 5 GeV=c.